Identification of a novel insect neuropeptide, CNMa and its receptor - Sung-Hwan Jung; Jae-Hyuk Lee; Hyo-Seok Chae; Jae Young Seong; Yoonseong Park; Zee‐Yong Park; Young‐Joon Kim (2014)
To identify ligands for orphan GPCRs, we searched novel neuropeptide genes in the Drosophila melanogaster genome. Here, we describe CNMa, a novel cyclic neuropeptide that is a highly potent and selective agonist for the orphan GPCR, CG33696 (CNMaR). Phylogenetic analysis revealed that arthropod species have two paralogous CNMaRs, but many taxa retain only one. Drosophila CNMa potently activates CNMaR‐2 from Apis mellifera , suggesting both receptors are functional. Although CNMa is conserved in most arthropods, Lepidoptera lack the CNMa gene. However, they retain the CNMaR gene. Bombyx CNMaR showed low sensitivity to Drosophila CNMa, hinting toward the existence of additional CNMaR ligand(s).